2012
DOI: 10.5012/bkcs.2012.33.6.1856
|View full text |Cite
|
Sign up to set email alerts
|

SnO2/SiO2Nanocomposite Catalyzed One-Pot Synthesis of 2-Arylbenzothiazole Derivatives

Abstract: SnO 2 /SiO 2 nanocomposite has been synthesized by using sol-gel method. Prepared catalytic materials has been well characterized by using X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), Fourier transform infrared spectroscopy (FT-IR), Brunauer-Emmer-Teller (BET) surface area, and temperature-programmed desorption of ammonia (NH 3 -TPD). SnO 2 /SiO 2 nanocomposite catalyzed synthesis of 2-arylbenzothiazoles by the cycloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Yelwande et al [208] have reported SnO 2 /SiO 2 nanocomposite as a new heterogeneous catalytic system for the preparation of 2-arylbenzothiazoles (19). Initially, the reaction was explored Scheme 23.…”
Section: Silica-supported Reagentsmentioning
confidence: 99%
“…Yelwande et al [208] have reported SnO 2 /SiO 2 nanocomposite as a new heterogeneous catalytic system for the preparation of 2-arylbenzothiazoles (19). Initially, the reaction was explored Scheme 23.…”
Section: Silica-supported Reagentsmentioning
confidence: 99%
“…Lande et al have developed a methodology based on simple condensation of 2-aminothiophenol and aromatic aldehydes for the synthesis of 2-arylbenzothiazoles using SnO 2 supported on SiO 2 (15 wt%) as a heterogeneous catalyst (Scheme 64) [85]. The catalytic activity of 15 wt% SnO 2 /SiO 2 was higher as compared to pure SnO 2 which gave lower yield of products at higher time range.…”
Section: Synthesis Of Benzothiazoles and Derivatives By Heterogeneousmentioning
confidence: 99%
“…Hence here we are interested to synthesized 2,4,5-triaryl-1Himidazoles using SnO2/SiO2 which is a mesoporous silica supported heterogeneous catalyst with large surface area, high thermal stability and having large range of tunable pores. As it is a nano-composite material show enhanced properties than those of the individual components used separately [18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%